Emotional maturity and marital readiness among marriage dispensation applicants - Putri, Nabila Triana; Pertiwi, Ratih Eka (Faculty of Psychology, Universitas Negeri Yogyakarta, 2024)
Child marriage is a marriage that occurs when one or both parties are under 19 years old, which requires marriage dispensation from a Religion Court judge. One of the problems faced by prospective brides is low marriage readiness. Marriage is important to prepare so that household life can run harmoniously. One of the important factors in marital readiness is emotional maturity. Emotional maturity plays an important role in marriage readiness for brides-to-be. This study examines the correlation between emotional maturity and readiness to marry in children applying for marriage dispensation. This study uses a correlational quantitative method. The sampling technique used quota sampling with predetermined criteria, namely the child applicant for marriage dispensation at the Malang Regency Religious Court, obtained 107 respondents. The instruments used in this study were the marital readiness and emotional maturity scales. The data analysis used was Pearson's product-moment correlation with a value of r = 0.455 and p < .001. This study's results indicate a significant and positive relationship between emotional maturity and readiness to marry in children applying for marriage dispensation.